Evaluation of the Impact of Different Pain Medication and Proton Pump Inhibitors on the Osteogenic Differentiation Potential of hMSCs Using 99mTc-HDP Labelling - Großner, Tobias; Haberkorn, Uwe; Gotterbarm, Tobias (Life, 2021)
First-line analgetic medication used in the field of musculoskeletal degenerative diseases, like Nonsteroidal anti-inflammatory drugs (NSAIDs), reduces pain and prostaglandin synthesis, whereby peptic ulcers are a severe adverse effect. Therefore, proton pump inhibitors (PPI) are frequently used as a concomitant medication to reduce this risk. However, the impact of NSAIDs or metamizole, in combination with PPIs, on bone metabolism is still unclear. Therefore, human mesenchymal stem cells (hMSCs) were cultured in monolayer cultures in 10 different groups for 21 days. New bone formation was induced as follows: Group 1 negative control group, group 2 osteogenic differentiation media (OSM), group 3 OSM with pantoprazole (PAN), group 4 OSM with ibuprofen (IBU), group 5 OSM with diclofenac (DIC), group 6 OSM with metamizole (MET), group 7 OSM with ibuprofen and pantoprazole (IBU + PAN), group 8 OSM with diclofenac and pantoprazole (DIC + PAN), group 9 OSM with metamizole and pantoprazole (MET + PAN) and group 10 OSM with diclofenac, metamizole and pantoprazole (DIC + MET + PAN). Hydroxyapatite content was evaluated using high-sensitive radioactive 99mTc-HDP labeling. Within this study, no evidence was found that the common analgetic medication, using NSAIDs alone or in combination with pantoprazole and/or metamizole, has any negative impact on the osteogenic differentiation of mesenchymal stem cells in vitro. To the contrary, the statistical results indicate that pantoprazole alone (group 3 (PAN) (p = 0.016)) or diclofenac alone (group 5 (DIC) (p = 0.008)) enhances the deposition of minerals by hMSCS in vitro. There is an ongoing discussion between clinicians in the field of orthopaedics and traumatology as to whether post-surgical (pain) medication has a negative impact on bone healing. This is the first hMSC in vitro study that investigates the effects of pain medication in combination with PPIs on bone metabolism. Our in vitro data indicates that the assumed negative impact on bone metabolism is subsidiary. These findings substantiate the thesis that, in clinical medicine, the patient can receive every pain medication needed, whether or not in combination with PPIs, without any negative effects for the osteo-regenerative potential.
Gesehen am 09.06.2021